Evaluating the severity of microvascular invasion in hepatocellular carcinoma, by probing the combination of enhancement modes and growth patterns through magnetic resonance imaging - Li Yanzhuo; Li Sijie; Lei Yan; Liu Lianlian; Song Bin (Radiology and Oncology)
Microvascular invasion (MVI), particularly its severity, correlates with prognosis in hepatocellular carcinoma (HCC), however, it remains uncertain which imaging traits are associated with MVI grades. Predicting MVI status precisely pre-surgery assists clinicians in making optimal treatment decisions.